Improving uniformity of CdS nanoparticle deposition on TiO2 nanotubes by enlarging the intertube space. (December 2013) - Liu, Lingjuan; Wang, Yan; Xu, Guangqing; Su, Lili; Lv, Jun; Wu, Yucheng
Highly ordered TiO2 nanotube arrays were fabricated via electrochemical anodization, and CdS nanoparticles were deposited on TiO2 nanotube arrays through sequential chemical bath deposition technique. The influence of water content on the intertube space and length and pore size of TiO2 nanotubes were studied systematically. The uniformity of CdS nanoparticles deposited on the TiO2 nanotube arrays with different intertube spaces was also investigated. The results show that when the water content increased from 2 to 10 vol.%, the shape of TiO2 nanotubes changed from hexagon to round with the increasing intertube space, and CdS nanoparticles could be deposited uniformly both inside and outside of TiO2 nanotubes when the water content was 10 vol.%.